2016
DOI: 10.4269/ajtmh.15-0815
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya and Dengue Virus Infections Among United States Community Service Volunteers Returning from the Dominican Republic, 2014

Abstract: Abstract. Chikungunya spread throughout the Dominican Republic (DR) after the first identified laboratoryconfirmed cases were reported in April 2014. In June 2014, a U.S.-based service organization operating in the DR reported chikungunya-like illnesses among several staff. We assessed the incidence of chikungunya virus (CHIKV) and dengue virus (DENV) infection and illnesses and evaluated adherence to mosquito avoidance measures among volunteers/staff deployed in the DR who returned to the United States during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…The necessity for and dearth of effective and approved treatments for acute viral infections was on full display after the Ebola outbreak in West Africa in 2014. The United States has also seen other mosquito-borne viruses (West Nile, dengue, and Zika viruses) emerge or re-emerge over the last twenty years, and effective antivirals against these viruses are direly needed as a matter of public health (Butterworth et al, 2016; Jones et al, 2016; Millman et al, 2016; Murray et al, 2010; Weaver et al, 2016). RNA viruses are inherently error prone, therefore they often quickly mutate in the presence of drugs that target viral proteins and viral enzymes (De Clercq, 2013; Flint SJR, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The necessity for and dearth of effective and approved treatments for acute viral infections was on full display after the Ebola outbreak in West Africa in 2014. The United States has also seen other mosquito-borne viruses (West Nile, dengue, and Zika viruses) emerge or re-emerge over the last twenty years, and effective antivirals against these viruses are direly needed as a matter of public health (Butterworth et al, 2016; Jones et al, 2016; Millman et al, 2016; Murray et al, 2010; Weaver et al, 2016). RNA viruses are inherently error prone, therefore they often quickly mutate in the presence of drugs that target viral proteins and viral enzymes (De Clercq, 2013; Flint SJR, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we found that one quarter of women of reproductive age traveling to Zika virus–affected countries in the Americas were traveling for mission or nonmedical service trips; another 15% were traveling for research or education. Previous studies show that volunteer travelers are likely to pursue health information but might not adhere to mosquito avoidance measures ( 11 , 12 ). A survey of volunteers traveling to the Dominican Republic in 2014 demonstrated that only 30% reapplied mosquito repellant, and <5% stayed in accommodations with screens ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Lalani et al 16 reported higher self-reported use of insect repellents on skin and clothing among travelers to regions with a malaria risk (53%) compared with regions with a Chikungunya/Dengue risk (16%). Although the use of mosquito repellents on skin and clothing is generally considered effective in preventing Chikungunya, its sociodemographic and behavioral correlates, particularly among US travelers to Caribbean destinations, has remained largely understudied.…”
mentioning
confidence: 99%
“…14 Among a sample of US travelers to the Dominican Republic, Millman et al 15 reported that, while approximately 95% of participants reportedly used insect repellent, only 30% applied it multiple times daily. 15 Lalani et al 16 reported higher self-reported use of insect repellents on skin and clothing among travelers to regions with a malaria risk (53%) compared with regions with a Chikungunya/Dengue risk (16%).…”
mentioning
confidence: 99%